The Paradox of Freedom in the Theodramatic Reflection of Hans Urs von Balthasar against the Background of the Thought of Henri de Lubac and Józef Tischner - Wołowski, Lech 1975- (2022)
The article examines the problem of paradoxicality of the notion of freedom in theodramatic approach of Hans Urs von Balthasar. The central subject concerns the paradox of finite freedom, infinite freedom and their relationship described in the second volume of Theo-Drama. The thought of the Swiss theologian is compared with the reflections of Henri de Lubac and Józef Tischner. The confrontation of the approaches of the above selected authors in the context of chosen topic made it possible to apply a new research method. Instead of the typically used in this context dialectical method, a method concentrated on identifying the paradox and exploring the mystery behind it has been applied. The most important results and conclusions include: a deeper understanding of the key role of dynamical nature of the finite freedom and demonstration of the importance of proper identification of its source; the demonstration of inalienable nature of the Christological dimension for understanding of the concept of the infinite freedom and resulting from it in-depth understanding of its essence; an in-depth insight into the conditions regarding the possibility of a genuine, though not symmetrical, relationship between the two freedoms.